Comparative Analysis Domino Logic Based Techniques For VLSI Circuit - Kamde, Shilpa; Shinde, Jitesh; Badjate, Sanjay; Hajare, Pratik (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Domino logic is a CMOS-based evolution of the dynamic logicÂ techniques Â basedÂ onÂ eitherÂ PMOSÂ orÂ NMOS transistors. Domino logic technique is widely used in modern digital VLSI circuit. Dynamic logic is twice as fast as static CMOS logic because it uses only N fast transistors. The Dynamic (Domino) logic circuit are often favored in high performance designs because of the high speed and low area advantage. Four different dynamic circuit techniques including Basic domino logic circuit are compared in this paper for low power consumption and speed of domino logic circuits. For digital circuit simulation used BSIM(Berkeley Short Channel IGFET ) Model because it control leakage current.